Antibacterial Activity Test of Ethanol Fraction of Moringa Leaves (Moringa oleifera L.) Against Staphylococcus aureus and Staphylococcus epidermidis - Dewi, Asiska Permata; Darmadi, Darmadi; Yesti, Yulia (Journal of Pharmaceutical and Sciences, 2023)
Moringa olifera L. is a herbaceous plant that consists of phytochemicals such as flavonoids, saponins cytokinins, acid-caffeoylquinic and contains unsaturated fatty acids such as linoleic (omega 6) and alfalinolenat (omega 3). This research aimed to determine the chemical compound content in the ethanol fraction of Moringa leaves and test its antibacterial activity against Staphylococcus aureus and Staphylococcus epidermidis. Phytochemical screening was carried out through a color reaction using a certain reagent; then the antibacterial activity test was carried out using the disc diffusion method with ethanol fraction concentrations of 15%, 30%, 45%, and 60%. The results showed that the compounds contained in the ethanol fraction of Moringa leaves were alkaloid, flavonoid, saponin, and tannin. The diameter of the inhibition zone for S. aureus bacteria is 7.43 mm – 10.16 mm, while for S. epidermidis bacteria is in the range 7.43 mm – 10.48 mm. It can be concluded that the ethanol fraction of Moringa leaves has antibacterial activity against S. aureus and S. epidermidis bacteria.